2015
DOI: 10.1016/j.ijscr.2014.10.097
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the middle rectum: Report of a case and literature overview

Abstract: HighlightsWe report a case of squamous cell carcinoma of middle rectum, with literature review (International Journal of Surgery Case Reports 2014; 5: 86–90).The report we describe was characterized by the presence of a squamous cell carcinoma of the middle rectum and a synchronous ureteral tumor.The patient had undergone pelvic irradiation for prostate cancer seven years before, thus suggesting aforementioned treatment as possible cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This theory is supported by the fact that squamous carcinoma is often found in the midst of poorly differentiated cells; 3. Michelassi et al (18) have suggested that epithelial damage causes proliferation of uncommitted basal cells into squa-mous cells which then undergo malignant transfor-mation; 4. Histological reviews of adeno-carcinomas have demonstrated areas of squamous differentiation, suggesting the possibility that these carcinomas may arise out of pre-existing adenomas or adenocarci-nomas (19).…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by the fact that squamous carcinoma is often found in the midst of poorly differentiated cells; 3. Michelassi et al (18) have suggested that epithelial damage causes proliferation of uncommitted basal cells into squa-mous cells which then undergo malignant transfor-mation; 4. Histological reviews of adeno-carcinomas have demonstrated areas of squamous differentiation, suggesting the possibility that these carcinomas may arise out of pre-existing adenomas or adenocarci-nomas (19).…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma (SCC) of the gastrointestinal (GI) tract most commonly occurs in the esophagus or anal canal, and prior studies report a <1% incidence within the rectum . Due to its rarity, the etiology of SCC of the rectum remains unclear, although it has been linked to chronic inflammation and prior radiotherapy . A recent Surveillance, Epidemiology, and End Results (SEER) analysis showed those with SCC to have a favorable prognosis compared to adenocarcinoma of the rectum .…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of rectal SCC are actually anal SCC with proximal extension into the rectum, which is different from primary SCC of the rectum. The estimated incidence of primary rectal SCC is approximately 0.01%–0.025% of all colorectal neoplasms [ 2 ]. William et al [ 3 ] established the following criteria to define SCC of rectal origin: (1) metastasis from other organs to the rectum must be ruled out; (2) there is an absence of anal involvement with SCC; and (3) an anal SCC-lined fistula with the rectum must be ruled out.…”
Section: Introductionmentioning
confidence: 99%